2017
DOI: 10.1016/j.fluid.2017.03.015
|View full text |Cite
|
Sign up to set email alerts
|

Indirect assessment of the fusion properties of choline chloride from solid-liquid equilibria data

Abstract: a b s t r a c tThe temperature and enthalpy of fusion of choline chloride -[Ch]Cl-are not directly measurable since this compound decomposes upon melting. Yet, given the wide use of this compound in the preparation of deep eutectic solvents (DES), its thermophysical fusion properties are very important for a better understanding of these mixtures and the thermodynamic description of their solid-liquid phase diagrams. In this work, the fusion properties of choline chloride were estimated using the solubility cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
105
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 79 publications
(127 citation statements)
references
References 26 publications
(24 reference statements)
8
105
3
Order By: Relevance
“…3, and in Fig. 2b Cl was also previously shown to behave ideally when mixed with choline chloride [23]. The explanation for the behaviour of [N 1,1,1,1 ]Cl is not yet clear.…”
Section: Resultsmentioning
confidence: 88%
See 1 more Smart Citation
“…3, and in Fig. 2b Cl was also previously shown to behave ideally when mixed with choline chloride [23]. The explanation for the behaviour of [N 1,1,1,1 ]Cl is not yet clear.…”
Section: Resultsmentioning
confidence: 88%
“…Cholinium chloride is an ionic solid commonly used in the preparation of deep eutectic solvents [19e21] since it not only forms biodegradable mixtures [22], but also acts as a hydrogen bond acceptor with a low melting enthalpy (4.3 kJ/mol) [23], which contributes to substantial melting-point depression of its mixtures. As such, in this work, the feasibility of using cholinium chloride to lower the melting point of organic chlorides, with a melting point too high to be useful as a solvent, is explored.…”
Section: Introductionmentioning
confidence: 99%
“…In this perspective, the decomposition of choline chloride upon melting would hamper any attempt to search for that method. Recently, however, Fernandez et al [17] were able to indirectly assess the melting temperature and enthalpy of choline chloride from solid-liquid equilibrium (SLE) data of a large number of systems. These properties were further appraised by Martins et al [2] Concerning the activity coefficients, the predictive model COSMO-RS, based on quantum chemistry, has been extensively used in the study of DES [18e29], but generally focusing in applications and/or specific systems and not in the analysis of phase diagrams, or in the prediction of eutectic points, as will be here explored.…”
Section: Introductionmentioning
confidence: 99%
“…They are reactive 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 4 species with high melting points and their isomerization and polymerization may take place upon heating leading to the formation of brown chromophores characteristic of sugar degradation. 14 An interesting review on the decomposition of sugars is reported by Roos et al 15 Due to the lack of experimental data, and the poor characterization of the thermophysical properties of pure sugars and other NADES precursors, namely cholinium chloride, 16 it is not surprising that attempts to describe the SLE of DES by equations of state or activity coefficient models are scarce too. Moreover the complexity of the interactions between the DES constituents 17 are often not easily represented by conventional models.…”
Section: Introductionmentioning
confidence: 99%